International managerial skill and big Colombian exporting firms' performance, 2006-2014 - Federico Alberto Merchán~Álvarez (The World Economy, 2024)
This paper uses a sample of the biggest private Colombian exporting firms to propose and estimate a two-step methodology for measuring international managerial skill and calculating its impact on international firm performance. The first step quantifies the managerial team's organisational capital contribution to rise firms' export proficiency through the average of a regression residuals group conformed by export unit value residuals for differentiated products (multiplying by -1 the price competition products' residuals) and export quantity residuals for homogeneous products. The second step results indicate that: (i) international managerial quality has a significant and robust positive effect on export value, (ii) better managers in the international market do not increase the number of products exported but upgrade export basket's quality and (iii) export value elasticity relative to international managerial quality is around 5 times larger than export value elasticity relative to exogenous global demand shocks.
Keywords: F23; F10; M11; M12; L25; 330; exporting; firm's performance; international experience; management practices; quality versus price competition